Symptoms of depression in autistic children and adolescents - Valles-Capetillo, Elizabeth; Argueta, Paula; Martin, Lucas A.; O’Kelley, Sarah; Kana, Rajesh K. (Frontiers in Psychiatry, 2025)
Depression is a frequently co-occurring condition in autism spectrum disorder (ASD). Notably, autistic individuals are approximately four times more likely to experience depression than the general population. Difficulties in emotion regulation, inhibitory control, and social skills, common in autistic individuals, are thought to contribute to increased risk and vulnerability to depression. The present study sought to examine the prevalence of depressive symptoms and its cognitive correlates in a sample of autistic and neurotypical (NT) children and adolescents (53 ASD and 43 NT). Data were collected using parent-report questionnaires that assessed depressive symptoms, executive functions, and social skills. Group differences and the relationship between depressive symptoms and cognitive measures were assessed by t-test and linear regression analyses respectively. The results indicated a significant increase in depressive symptoms among the autistic, compared to NT, participants (p < 0.0001). Moreover, emotion regulation and social communication and interaction were significantly associated with depressive symptoms in both groups (p < 0.05). Additional analysis revealed that parental stress did not influence the relationship between executive functioning and interaction and depressive symptoms in both groups. But parental stress influenced the relationship between social communication and interaction and depressive symptoms. The present study highlights the dual contributions of emotional regulation and SCI to depression in both autistic and NT population. Furthermore, underscore the importance of addressing emotion regulation and social communication in identifying risk factors of depression and developing intervention strategies for depression.